2009
DOI: 10.1149/1.3196246
|View full text |Cite
|
Sign up to set email alerts
|

Efficient SWCNT-Based Anode for DMFC Applications

Abstract: Carbon Vulcan XC72 is still considered as the standard catalyst support in gas diffusion electrodes for low temperature polymer fuel cell applications. Because of its relatively low specific area and poor corrosion resistance, alternative materials such as carbon nanotubes (CNTs) are currently the focus of numerous investigations. This work reports on the test of single-walled carbon nanotubes (SWCNTSs) as Pt and PtRu catalyst support in the direct methanol fuel cell (DMFC) anode. After the treatment of the CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Similarly, Dillert et al [14] found improved performance with oxidized SWCNTs as support material. On the other hand, Cui et al [15] showed that PtRu supported on MWCNTs provide 33% better power density than a commercial catalyst.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Dillert et al [14] found improved performance with oxidized SWCNTs as support material. On the other hand, Cui et al [15] showed that PtRu supported on MWCNTs provide 33% better power density than a commercial catalyst.…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, with the aim of enhancing activity and stability of direct methanol fuel cell (DMFC) electrodes, different carbon supports have been investigated such as single-walled (SW-) and multiwalled (MW-) carbon nanotubes (CNTs), graphene, carbon nanofibers (CNFs), fullerenes, carbon nanohorns and mesoporous carbon [8][9][10][11][12]. Specifically CNTs [13][14][15] and CNFs [16][17][18] have been studied as catalysts supports because of their outstanding conductivity, thermal and mechanical stability [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, among those, the carbon nanofibers were the most studied in DMFC. Drillet et al [30] analyzed the performance of SWCNTs, produced by the arc-discharge method, as catalyst support in the anode side of fuel cell. They used hot air (300 C) or concentrated nitric acid as activation treatments to promote the catalyst anchoring.…”
Section: Carbon Nanotubes and Nanofibersmentioning
confidence: 99%
“…Although many of these alternative supports have been tested in DMFC [103][104][105][106][107][108][109][110][111][112][113][114][115][116][117], their long-term stability in DMFC conditions has not been studied widely though it is a significant reason for their research [33,118]. In light of this, Vulcan-, GNF-and FWCNT-PtRu were tested for a period of 3 days in a micro-DMFC anode in Publication IV.…”
Section: The Role Of Carbon Supportmentioning
confidence: 99%
“…However, this has not been widely investigated in the literature (Publications II, III and IV) [33,107,117] as most studies of different catalyst supports in a DMFC only report the performance [103][104][105][106][108][109][110][111][112][113][114][115][116]. In Publication IV, three…”
Section: Carbon Supportsmentioning
confidence: 99%